IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN PASAR SANGKUMPAL BONANG KOTA PADANGSIDIMPUAN TAHUN 2013-2015 - Muhammad Yusuf Harahap; Baskoro Wicaksono (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2016)
research present describe the implementation of Sangkumpal Bonang markets retribution policy in Padangsidimpuan City in 2013-2015. In region autonom, the Regency Government have a authority to increase of regency saving by market retributions. In Padangsidimpuan City market retributions have based on district regulation Number 4 in 2010 about retributions of public services.The research use the methode are qualitative methodes that analyze problem research by describe the subject and object conditions based on real fact. This research use location in Padangsidimpuan city and researcher collect data from books, government regulation, jurnal, mass media, website and deep interview with informan likes Head of coperation, Economic creative, industry, trade and market of Padangsidimpuan, Head of Unit Retribution Marekt, Head of section Market, staff of retribution and seller in Sangkumpal Bonang Markets.The conclution of this research are the implementation of Sangkumpal Bonang markets retribution policy in Padangsidimpuan City have done since 2009 and it’s not optimally. Some factos cause low of socialization about regulation market retributions, low of staff quantity and intensif for staff retribution, low of controlling from coperation, Economic creative, industry, trade and market of Padangsidimpuan agency, low of attention seller to pay the market retributions and, so many illegal seller in Sangkumpal Bonang that not payed the retributions.Keywords: implementation, policy, retributions and market.